«Gay was a thing for big places»: metronormativity, sexile and agency in two Spanish neorural novels - Corrales Díaz-Pavón, José (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article presents a contrastive analysis of two novels, Bird's Nest by Luis Maura and The stain by Enrique Aparicio Esnórquel. Both novels review, from an adult perspective, the socialisation of their protagonists as adolescents and homosexual men in a rural space. The socialisation of the protagonists will be shaped by a metronormative understanding of the relationship between the rural and the queer. This perspective views the urban space as a domain of sexual and affective divergence and posits that the natural trajectory for rural LGTBI individuals is sexile. In these two novels there is a dialogue with this idea, either to confirm it, as will happen in Bird's Nest, or to deconstruct it, as happens in The stain. The contrast between them demonstrates that the literary representation of sex-gender dissidence is not limited to accepting an imaginary that constrains the agency of queer people linked to rural areas to sexile. Rather, alternative ways of representing queer existences in non-urban spaces can be conceived.
Keywords: neorural narrative; homosexuality; metronormativity; sexile; agency